DFT-BASED INVESTIGATION OF CARBON DIOXIDE REDUCTION REACTION ACTIVITY AND SELECTIVITY TO CO AND HCOOH IN NICKEL PHOSPHATE TRANSITION METAL ALLOYS - Rifqy Maulana, Muhammad
To reduce the concentration of CO? in the atmosphere, one approach that can be undertaken is the utilization of CO? through various methods. One promising technique is the electrochemical reduction of CO?. This process requires an electrocatalysis system with a catalyst that exhibits high selectivity and low overpotential. In several other reactions, Nickel (II) Phosphate has shown great potential due to its superior performance as catalyst for hydrogen evolution reaction and oxygen evolution reaction. However, studies on the use of NiPO as a catalyst for CO? reduction reactions are not yet available, leaving the catalytic activity of this material in such reactions unknown. In this study, the catalytic activity and selectivity of nickel phosphate (Ni3(PO4)2) and bimetallic nickel phosphate (NiMPO, M = Mn, Fe, Co, Cu) surfaces for the CO2 reduction reaction (CO2RR) are studied using density functional theory (DFT) calculations. Our results indicate that alloying NiPO with transition metals significantly lowers the limiting potentials for CO2RR to CO and HCOOH, compared to the pure NiPO surface. Although complete suppression of the competing hydrogen evolution reaction (HER) was not achieved, the bimetallic NiMPO surfaces showed enhanced catalytic activity and a reduced limiting potential difference between CO2RR and HER. Among the tested configurations, the Ni site of NiFePO(100) was identified as the most promising for CO production, while the Fe site on NiFePO(100) demonstrated strong activity for HCOOH formation. These findings suggest that specific paduan configurations can improve both the activity and selectivity for CO2RR, offering a promising route for the development of efficient electrocatalysts for sustainable CO2 conversion. Keywords: CO2RR, Nickel Phosphate, CO Formation, HCOOH Formation, DFT